Serum uric acid to creatinine ratio in patients with early-onset post-stroke cognitive impairment: a retrospective cohort study - Liao, Libin; Huang, Weiquan; Ma, Rongchao; Hu, Wentong; Wu, Hui; Su, Moxi; Sha, Dujuan (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive impairment is the major complication of acute ischemic stroke, which is a significant health concern imposing a heavy economic burden on families and society. Studies have shown that the serum uric acid (SUA) level is correlated to clinical outcomes of stroke and neurogenerative diseases. The serum uric acid to serum creatinine ratio (SUA/SCr) is an independent risk factor for poor outcomes of acute ischemic stroke and can potentially become an effective diagnostic indicator for cognitive decline. In this study, we aimed to investigate the association between SUA/SCr and early-onset post-stroke cognitive impairment.MethodsConsecutive acute ischemic stroke patients from our hospital were enrolled between June 2023 and September 2024. All blood samples were collected within 24 h after admission, and the cognitive function of patients was assessed within 2 weeks using the Chinese version of the Montreal Cognitive Assessment (MoCA). SUA/SCr was calculated by serum uric acid (umol/L)/serum creatinine (umol/L) and was split into three layers according to tertiles. The subjects were divided into a post-stroke cognitive impairment group and a non-post-stroke cognitive impairment group based on cognitive assessment. Binary logistic regression with different models, multivariate logistic regression analysis, and receiver operating characteristic (ROC) curves were adopted to evaluate the predictive ability of SUA/SCr in early-onset post-stroke cognitive impairment.ResultsThe current study showed that the post-stroke cognitive impairment group had lower SUA/SCr (p = 0.005) and the lower tertile of SUA/SCr is associated with a higher prevalence of post-stroke cognitive impairment (p = 0.008). The multivariate logistic analysis indicated that SUA/SCr (OR = 0.560, 95% CI = 0.321–0.976, p = 0.024) was independently associated with early-onset post-stroke cognitive impairment, and the lowest tertile was independently associated with a 5.903-fold increased risk of post-stroke cognitive impairment after adjusting for confounders. The optimal cutoff value of SUA/SCr to predict post-stroke cognitive impairment was 4.874, which gave a sensitivity of 72.22% and a specificity of 63.16%.ConclusionOur study revealed that SUA/SCr can be a potential indicator for post-stroke cognitive impairment in the early phase, a lower level of SUA/SCr upon admission was independently correlated to cognitive dysfunction after stroke.